Blount's disease: The importance of early diagnosis and early treatment. Issue 7 (20th May 2019) - Delniotis, Ioannis; Leidinger, Benedikt; Kyriakou, Aikaterini; Galanis, Nikiforos
Abstract: The purpose of this image is to raise awareness of the early diagnosis and treatment of Blount's disease. Failure to distinguish between physiologic genu varum and early onset of Blount's disease can lead to irreversible outcomes, including progressive deformity with gait deviations, limb‐length discrepancy, and premature arthritis of the knee. Abstract : The purpose of this image is to raise awareness of the early diagnosis and treatment of Blount's disease. Failure to distinguish between physiologic genu varum and early onset of Blount's disease can lead to irreversible outcomes, including progressive deformity with gait deviations, limb‐length discrepancy, and premature arthritis of the knee.